PERAN PETANI BAWANG MERAH DALAM MENINGKATKAN EKONOMI RUMAH TANGGA PETANI DI DESA TEKO KECAMATAN PRINGGABAYA KABUPATEN LOMBOK TIMUR: The Role And Contribution Of Shallot Farmers In Improving The Household Economy Of Farmers In Pringgabaya District, East Lombok Regency - Suriadi, Ahmad; Hamsyuni, Muhammad; Elitamaydasari, Elitamaydasari (Ganec Swara, 2025)
The objectives of this study: 1). To determine the role of shallot farming in improving the household economy (RT) of farmers in Pringgabaya District, East Lombok Regency. 2). To determine what factors hinder shallot farming in Pringgabaya District, East Lombok Regency. The study was conducted in Batuyang Village, Pringgabaya District, East Lombok Regency. The study began in July 2025 until August. This type of research is Qualitative. To obtain data, the author conducted observations, interviews, questionnaires and documentation studies. The results of the study: (1) The role of shallot farming in improving the economy of farmer families (case study of Pringgabaya District, East Lombok Regency), that shallot farming can improve the economic standard of living of farmer families. (2) The obstacles faced by farmers in shallot farming are the scarcity of basic materials for shallot farming needs such as fuel (gasoline) scarcity, fertilizer scarcity, and the high price of medicines. The unstable price with the results obtained from shallot farming, thus affecting the economic sustainability of farmers’ households. From the results of the study, it can be concluded that: (1) the regional government of East Lombok Regency must issue a policy that will regulate the stability of shallot prices. (2) to all farmers who have shallot farming businesses to actively participate in determining prices according to the costs they incur during the shallot farming process.